(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2025)
Background: Current hypertension guidelines recommend combining both the office (clinic) BP and out-of-office (home) BP to diagnose hypertension. This study was designed to explore masked hypertension in the young adult population of a defined community by home blood pressure monitoring (HBPM). Methodology: It was a community-based, prospective, observational study conducted by the hypertension study group, Chattagram International Medical College at Ward number 4 (Chandgaon), Chattogram City Corporation, Chattogram from May 15, 2023, to September 14, 2023. Young adults of 18 to 35 years with no history of hypertension, not on any antihypertensive, with clinic BP measurement <140/90 mm Hg and who consented were included in the study. After taking HBPM recording twice daily for seven successive days, the participant returned to the clinic with the completed HBPM chart and returned the devices. The data were analyzed; masked hypertension was labelled when clinic blood pressure measurement was less than 140/90 mmHg and average HBPM monitoring was ≥135/85 mm Hg. Result: A total of 327 participants were enrolled, and 11 cases were excluded. Among 316 participants, 55% were male and 45% were female, mean age was 26.77±5.6 years. Among all, 12 (3.8%) participants were proven to have masked hypertension. Among those with masked hypertension, the mean age was 31.42±7.09 years, males and females were 58% and 42% respectively, the mean BMI was 28.53±5.25kg/m2, mean home blood pressure monitoring (HBPM) was 139.96/88.79 (±1.85/2.98) mm Hg. The factors significantly related to masked hypertension were age >30 years, high BMI (>25 Kg/m2), high clinic BP, sedentary lifestyle, diabetes mellitus, positive family history and smoking. Conclusion: This study emphasizes home blood pressure monitoring for identifying masked hypertension in selected cases; future research is recommended to develop optimal screening strategies. J Bangladesh Coll Phys Surg 2025; 43: 190-196